Current Practice of Imaging-Guided Interventional Procedures in Rheumatic and Musculoskeletal Diseases: Results of a Multinational Multidisciplinary Survey - Carubbi, Francesco; Bosch, Philipp; Machado, Pedro M.; Scirè, Carlo Alberto; Alunno, Alessia; Proft, Fabian; Baraliakos, Xenofon; Dejaco, Christian (Frontiers in Medicine, 2021)
Objectives: To investigate opinion and routine practice of specialists from different disciplines on imaging techniques for interventional procedures related to rheumatic and musculoskeletal diseases (RMDs). Methods: An English-language questionnaire was developed by an international working group and distributed to health care providers of various disciplines involved in the care of people with RMDs via an online survey tool (SoSci Survey®) from December 2019 to May 2020. Results: A total of 1,105 respondents from 56 countries completed the survey, over 60% of participants were rheumatologists. The majority of respondents (88%) performed interventional procedures in RMDs patients and 90% of them used imaging guidance. Ultrasonography was the most frequently used technique, particularly among rheumatologists. X-ray and computed tomography were mainly used by radiologists. A discrepancy emerged between the importance assigned to certain items such as the availability of a second operator and their actual implementation in clinical practice. Local barriers, lack of resources and facilities were mentioned as the most relevant obstacles in this regard. Lack of training on imaging and/or imaging guided procedures did not emerge as a barrier to perform such interventions; in fact, 19% of respondents performing the procedures indicated not to have received adequate training in this field. Conclusions: This is the first multinational multidisciplinary survey exploring in detail the opinions and practice on imaging guidance for interventional procedures in RMDs. A harmonization of protocols based on international guidelines, along with adequate training programmes and interventions on barriers at national/local levels are the main unmet needs requiring attention.